Check the picture below
notice, using the 30-60-90 rule, since that triangle is a 30-60-90 triangle, we get 11 = 2x
4(a+12)=32
4a+48=32
4a=-16
a=-4
Answer:
Step-by-step explanation:
18-(+5-4)+7
18-1+7
18+6
24
Answer:
Option C.
Step-by-step explanation:
Shortest way to solve this question is to find the factors of the given expression.
The given expression is (x² + 13).
Now we have to factorize it.
(x² + 13) = x² + (√13)²
= x² + [-(i)²√(13)²] [Since i = √(-1)]
= x² - (i√13)²
= (x - i√3)(x + i√3) [Since (a² - b²) = (a + b)(a - b)]
Option C will be the answer.
Y = a(b^x)
y=mx + b is the equation of a line. It is a linear function because it has a constant rate of change.
y = a(b^x) is an exponential function because it has has an exponent and its rate of change is not constant